Retrospective analysis of the progression of early dry age-related macular degeneration in patients receiving versus not receiving a multi-component nutraceutical for four years - Lutsenko, N. S.; Rudycheva, O. A.; Isakova, O. A.; Kyrylova, N. S.; Луценко, Ніна Степанівна; Рудичева, Ольга Анатоліївна; Ісакова, Оксана Анатоліївна; Кирилова, Тетяна Сергіївна (My University, 2023)
Purpose: To retrospectively analyze the optical coherence tomography (OCT) changes in retinal morphology and progression in these changes in patients with early dry age-related macular degeneration (AMD) receiving versus not receiving a multi-component nutraceutical daily for four years. Material and Methods: We retrospectively analyzed disease progression in 52 patients (98 eyes) with early dry AMD who had been regularly followed up for four years. Group 1 was comprised of 24 patients (98 eyes) who had been receiving vitamin and mineral tablets containing the AREDS2 formulation plus resveratrol and vitamin D daily for four years. Group 2 was comprised of 28 patients (53 eyes) who had not been receiving any nutritional supplement. Retinal morphology was assessed by OCT and OCT angiography. Results: In group 1, best-corrected visual acuity (BCVA) did not change after completion of the 4-year observation period compared to baseline (0.6 ± 02, p = 0.72). In group 2, BCVA was 0.6 ± 0.2 at baseline and decreased to 0.2 ± 0.2 in four years (p ≤ 0.001). In patients with a low to moderate risk of progression in groups 1 and 2, the four-year progression rate was 15.4% and 45.4%, respectively, which corresponds to an annual progression rate of 3.8% and 11.3%, respectively. In patients with a high risk of progression in groups 1 and 2, the four-year progression rate was 26.3% and 80%, respectively, which corresponds to an annual progression rate of 6.5% and 20%, respectively. Patients who had early dry AMD eyes with a low to moderate risk of progression (and a high risk of progression) at baseline and were not taking the nutritional supplement, had 4.58 greater odds (95% CI, 1.291 – 16.267; р = 0.018) [and 11.2 greater odds (95% CI, 2.505 – 50.081; р = 0.0016)] of having AMD progression than those receiving the nutritional supplement daily for four years. Conclusion: A regular intake of tablets containing the AREDS2 formulation plus resveratrol and vitamin D slows the progression of early dry AMD, especially in eyes with a high risk of disease progression, and contributes to the preservation of visual function.
Keywords: age-related macular degeneration; nutraceutical; progression; optical coherence tomography; changes in retinal morphology